Project management in academic physical education system: benefits analysis - Babintsev, V.P.; Goncharuk, S.V.; Peresypkin, A.P.; Goncharuk, Y.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze benefits of a project management technology for the modern academic physical education system. Methods and structure of the study. We run, for the purposes of the study, the academic physical education system Management Survey in the Belgorod, Kursk and Lipetsk Oblasts using a questionnaire survey of the academic physical education system communities and focus group interviews. We sampled students (n=1000), faculties and researchers (n=300), and university management (n=140). The survey was designed to find attitudes of the academic physical education system communities to the academic physical education system management system and potential benefits of the modern project activity for the latter. Results and conclusion. We found the project management technology being potentially beneficial for the academic physical education system, conditional on the sound institutional and technological provisions analyzed herein.